Making Seed Systems and Markets for Vegetatively Propagated Crops (VPCs) Work for the Poor: A Cross-Country Study of Kenya, Nigeria, and Vietnam - International Food Policy Research Institute; International Center for Tropical Agriculture; International Institute for Tropical Agriculture; International Potato Center; Michigan State University (International Food Policy Research Institute, 2019)
Many developing-country farmers cultivating vegetatively propagated crops (VPCs)—crops such as cassava, potato, sweetpotato, and yam—face constrained access to quality planting material. This challenge is distinct from the challenges facing cereal crops, and is associated with both the unique biological and economic nature of vegetative propagation. Although technological solutions exist, there are other limiting factors relating to policies, institutions, and markets that shape VPC seed systems, e.g., quality assurance mechanisms, certification regulations, sanitary and phytosanitary standards, and plant variety protection. This research project aims to provide actionable evidence on policy and investment options to accelerate seed system and market development in countries where VPCs are important to food security and agricultural development. By taking a collaborative and multidisciplinary approach to the research, the project (1) analyzes current policy initiatives and success factors underpinning models that incentivize cost-effective multiplication and distribution of VPC seed to smallholders; and (2) develops a set of crop-specific case studies in Kenya, Nigeria, and Vietnam that encourage closer consideration of more appropriate policy options. This document provides a brief summary of the project and accompanies the key informant interview guides to collect data for analysis purposes.